WORKSHOP ON APPLICATIONS PAYROLL (STEAM) CV. S & D JAYA - Leonita Dewanti; Sahni Damerianta, SKom, MMSI (Jurnal Sistem Informasi, 2003)
In a small and large companies require payroll processing is right - deadly accurate from the datas of each employee starts the way it works until the absence of a superior to subordinates sari payroll of each employee must vary to obtain accurate calculations should therefore relate to the employee services . Therefore, the payroll in the computer system is helping the financial administration to proceed in this case a "CV. S & D JAYA "need to use a computer from a manual to computerized, because it requires field employees process more effective and efficient.